Large variability found in musculoskeletal physiotherapy scope of practice throughout WCPT and IFOMPT affiliated countries: An international survey. (July 2019) - Froment, Frédéric P.; Olson, Kenneth A.; Hooper, Troy L.; Shaffer, Stephen M.; Sizer, Phillip S.; Woodhouse, Linda J.; Brismée, Jean-Michel
Abstract: Background: Advanced practice physiotherapy (APP) rights are part of the evolution of the Physical Therapy profession. To date, no study has investigated musculoskeletal APP rights within the World Confederation for Physical Therapy (WCPT). Objective: To investigate musculoskeletal APP rights for physical therapists worldwide and examine the relationship between level of education (entry and post-professional) and direct access for countries that are vs. are not members of the International Federation of Orthopaedic Manipulative Physical Therapists (IFOMPT). Design: Cross-sectional study with descriptive and exploratory online surveys. Methods: An electronic survey-based descriptive and exploratory investigation was conducted. We assessed variability between WCPT member organizations descriptively and the strength of the relationships among the number and types of APP rights with: (1) country affiliation to IFOMPT; (2) entry-level professional degree; (3) post-professional training; and (4) direct access. Results: Some countries reported having the right to practice all 20 APP rights while others reported no APP rights. Countries with IFOMPT member organization countries displayed fair correlation (rs  = .48, p < .03) between entry-level physical therapy degrees and number of APP rights. IFOMPT member organization countries were less likely to require post-professional training for direct access and manipulation. Conclusion: APP rights for countries with direct access were significantly higher than for countries without direct access. IFOMPT member organizations demonstrated higher APP rights prevalence and were less likely to require post-professional training to obtain the right to direct access and perform manipulation. Highlights: There is large variability in physical therapy scope of practice between countries. PTs in countries with direct access display larger scope of practice. Direct access is more prevalent in IFOMPT MOs. The number of APP rights allowed in each country is a multifactorial process.